Extent of Knowledge of Fish Farmers About Scientific Fish Culture Practices in North 24 Parganas of West Bengal, India - B. Goswami , S. B. Mukhopadhyay; S.S. Dana (Indian Journal of Extension Education, 2016)
The study was conducted in North 24 Parganas district of West Bengal. It was found that majority of the fish farmers (50.8%) had medium level of knowledge regarding scientific fish culture practices. The highest extent of knowledge was observed in the names of some aquatic weeds (95.83%), and lowest was observed in the minimum depth of water required for fish culture and the time gap required between manure application and stocking of fish seed (26.67%). The path analysis indicated that innovative proneness was the most potent variable in affecting the knowledge of fish farmers positively